(untitled) (diségno, 2023)
Deception and mathematical rigor: two seemingly antithetical dimensions. Yet sometimes oxymorons are reconciled. This is the subtext of the exhibition Jean François Niceron and Emmanuel Maignan. Two Minims, between Science and Faith, curated by Alessio Bortot, Agostino De Rosa and Imago rerum, which opened on October 7, 2023, at the shrine of St. Francesco di Paola [1]. The exhibition traces the studies carried out by the two French Minims in the 17th century between the convent of SS. Trinità dei Monti in Rome and the Mother House of the Minims in place Royale (now place des Vosges) in Paris, which was almost destroyed in the late 19th and early 20th centuries. [read more]